The Effect of Chicken and Cow Manure Dose Combination on The Growth and Production of Red Chili (Capsicum annum L.) - Yusnaeni, Yusnaeni; Sumiyati, Sri; Lion, Thomas; Nubatonis, Richnal (Universitas Sembilanbelas November Kolaka, 2021)
Chili is one of the plants that are needed by the community so that proper cultivation techniques are needed, in this case related to fertilization by utilizing organic animal waste.This study aims to determine the response of the growth and production of red chili (Capsicum annum L.) to chicken and cow manure dose combination. The method used is an experimental method with a factorial completely randomized design which consists of two factors, namely the first factor is the type of animal manure which consists of two levels, namely cow dung and chicken manure, the second factor is the dose of fertilizer there are three levels, namely 200 grams, 300 grams and 400 grams. The total combination of treatments was 9 treatments and 3 replications so that in total there were 27 units. The parameters observed were chili growth (height and number of branches) and chili production (number of fruits and fruit weight). The data were analyzed of variance with 5% and 1% levels, followed by Duncan's 5% further test. The results of the analysis showed that the combination of treatments had a very significant effect on plant height and fruit number (12.77 and 5.00), significantly affected the number of fruits (3.55), but did not affect the wet weight of fruit (2.46).Further test results showed that the best treatment for the parameters of plant height, number of branches, and number of fruit was a combination of 300 grams of chicken manure and 200 grams of cow manure.Â Keywords: dose, chicken manure, cow manure, growth, productionÂ